The challenges of employability among UiTM graduates in oil and gas industry / Nurul Farhana Mohd - Mohd, Nurul Farhana (2015)
The aim of this study is to determine the challenges of employability among UiTM graduates in oil and gas industry. Due to too many graduates supply, there could incurred the challenges of employability especially among UiTM graduates as my subject for this study. There are several issues that have been identified for the challenges that faced by UiTM graduates such as marketability, employability skills and employers‟ needs/requirements. The outcomes have been confirmed where employers‟ needs is the most important issues that graduates need to be more focus on. So that they can prepare well on how to attract the employers attentions to them by understand the employers‟ needs.